2013
DOI: 10.1159/000338993
|View full text |Cite
|
Sign up to set email alerts
|

Mild Improvement in Symptoms and Pulmonary Function in a Long-Term Follow-Up of Patients with Toluene Diisocyanate-Induced Asthma

Abstract: Background: Long-term follow-up of diisocyanate-induced occupational asthma has been occasionally reported. Methods: We studied the outcome of toluene diisocyanate (TDI)-induced asthma in 46 patients at diagnosis and after a follow-up of 11 ± 3.6 years. Symptoms, anti-asthma therapy, forced expiratory volume in 1 s (FEV1) and bronchial hyperresponsiveness to methacholine were assessed. Results: A significant improvement in FEV1 (% predicted) and PD20FEV1 methacholine was observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
(27 reference statements)
1
1
0
Order By: Relevance
“…TDI-induced asthma is characterized by AHR, Th2-dominated airway inflammation and granulocytic infiltration (15,16) and is often associated with a poor prognosis. Airway inflammation tends to persist despite inhaled steroid medication even after the cessation of the exposure (17,18). Although there is debate concerning its etiopathogenesis, in our study, mice with TDI-induced asthma displayed similar characteristics as those of affected patients: AHR and inflammatory cell infiltration, higher levels of serum IgE, as well as an imbalanced Th1/Th2 response.…”
Section: Discussionsupporting
confidence: 48%
“…TDI-induced asthma is characterized by AHR, Th2-dominated airway inflammation and granulocytic infiltration (15,16) and is often associated with a poor prognosis. Airway inflammation tends to persist despite inhaled steroid medication even after the cessation of the exposure (17,18). Although there is debate concerning its etiopathogenesis, in our study, mice with TDI-induced asthma displayed similar characteristics as those of affected patients: AHR and inflammatory cell infiltration, higher levels of serum IgE, as well as an imbalanced Th1/Th2 response.…”
Section: Discussionsupporting
confidence: 48%
“…Several studies of workplace interventions for OA were published after the 2011 review. With a comprehensive approach of including recently published studies, [9][10][11][12] along with those studies already identified in the 2011 Cochrane review, we produced an updated systematic review of evidence on the effectiveness of workplace interventions for the treatment of OA. 13…”
Section: Introductionmentioning
confidence: 99%